S-Mixing Tuple of Operators on Banach Spaces. (20th October 2016) - Wang, Wei; Shu, Yonglu; Wang, Xingzhong
Abstract : We consider the question: what is the appropriate formulation of Godefroy-Shapiro criterion for tuples of operators? We also introduce a new notion about tuples of operators, S -mixing, which lies between mixing and weakly mixing. We also obtain a sufficient condition to ensure a tuple of operators to be S -mixing. Moreover, we study some new properties of S -mixing operators on several concrete Banach spaces.